Fire in the round: A holistic approach to the Lower Palaeolithic record. (June 2021) - Scott, Rebecca V.; Hosfield, Rob
Highlights: Review of European Lower Palaeolithic fire evidence. Posits two heuristic models of fire needs and likely settings. Key issues for understanding the Lower Palaeolithic fire record are highlighted. Recommends a 'holistic' approach to understanding the needs for and use of fire. Abstract: Whilst several explanations have been proposed for the absence of fire-related behaviours at well preserved Lower Palaeolithic sites, much of the emphasis of previous research has concentrated on our ability to find fire in the archaeological record. Furthermore, evolutionary models of early hominin fire engagement have often been developed and discussed in the context of early African hominins. Here we explore the role of fire in the behaviours, choices and lives of hominins during the earliest occupations of temperate regions, with a focus on Europe. We consider fire use in the context of Europe's specific palaeoenvironmental conditions and discuss whether a long or short fire chronology model best fits the current evidence for the use of controlled fire in these regions during the Lower Palaeolithic. We propose two models for hominin fire behaviours in the temperate latitudes, using a heuristic 'macroscale to microscale' approach to understanding the needs for — and the use of — fire during this period. We argue that such holistic approaches must combine experimental work, experiential observations and cost-benefit approaches and should consider site context and function, fire function, social behaviour, and mobility, to evaluate the limited evidence for fire use in the Lower Palaeolithic. We highlight that, varying with seasonality, fire function (and the associated costs and benefits) was of particular importance and may explain the overall paucity of evidence for fire use in temperate regions prior to the Middle Palaeolithic. This has implications for other potential survival strategies that are invisible in the early archaeological record, such as shelter, clothing, and the putrefaction of meat for later consumption.